2016
DOI: 10.1016/j.tem.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Effects of PPARβ/δ on Insulin Resistance and Cardiovascular Disease

Abstract: Insulin resistance precedes dyslipidemia and type 2 diabetes mellitus (T2DM) development. Preclinical evidence suggests that peroxisome proliferator-activated receptor (PPAR) β/δ activators may prevent and treat obesity-induced insulin resistance and T2DM, while clinical trials highlight their potential utility in dyslipidemia. This review summarizes recent mechanistic insights into the antidiabetic effects of PPARβ/δ activators, including their anti-inflammatory actions, their ability to inhibit endoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 94 publications
2
52
0
1
Order By: Relevance
“…In recent years there has been a great interest in the actions of PPARα and PPARγ. PPARδ has roles in metabolism similar to PPARα and PPARγ such as improving glycemic control, decreasing insulin resistant and elevating high-density lipoprotein [4951]. In addition, PPARδ was reported to have pro-angiogenic effects [5] unlike PPARα and PPARγ [52].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there has been a great interest in the actions of PPARα and PPARγ. PPARδ has roles in metabolism similar to PPARα and PPARγ such as improving glycemic control, decreasing insulin resistant and elevating high-density lipoprotein [4951]. In addition, PPARδ was reported to have pro-angiogenic effects [5] unlike PPARα and PPARγ [52].…”
Section: Discussionmentioning
confidence: 99%
“…PPARδ (also known as PPARβ) is ubiquitously expressed and when activated it promotes fatty acid oxidation, thermogenesis, insulin sensitivity, high density lipoprotein cholesterol (HDLc) levels in plasma and overall energy expenditure 7 . PPARδ deficient mice are prone to obesity and insulin resistance when challenged with a high-fat diet (HFD).…”
Section: Introductionmentioning
confidence: 99%
“…PPARβ/δ activation inhibits human macrophage foam cell formation and inflammation induced by VLDL and it also exerts favorable effects on HDL-C level [41]. Moreover, relevant study showed that PPARβ/δ agonist treatment decreased plasma TG, Apo-B, total and LDL-cholesterol [42].…”
Section: Discussionmentioning
confidence: 99%